Life cycle assessment of earth-based residential unit “TOVA”: A 3D printed on-site load-bearing structure - Deena El-Mahdy; Eugene Marais; Marwa AbdelRahim; Alexandre Dubor; Edouard Cabay (Case Studies in Construction Materials)
This paper aims to assess the environmental life cycle of a real lead-bearing 3D printed earthen-based (3DP-E) structure built on-site, “TOVA” in Spain. The method followed a cradle-to-site approach focusing on wall structure. Three different structure scenarios are compared with the 3DP-E; conventional fired bricks construction, 3DP concrete (3DP-C), and 3DP-E (optimised). The results show that the conventional structure scenario is the highest impact in all the indicators. Global warming indicates the highest results in the conventional method than the 3DP methods with a value of 12004.5 kg CO2 eq, while 264.759 kg CO2 eq, 161.368 kg CO2 eq, and 592.995 kg CO2 eq, respectively for the 3DP-E, 3DP-E(O), and 3DP-C respectively. A significant environmental enhancement in global warming for 3DP-E and 3DP-E(optimized) are 55 % and 72 % respectively compared to 3DP-C, and around 97 % enhancement compared to the conventional technique. Regarding the carbon emission from transportation, 3DP-E recorded the lowest ratio from transportation, as 85 % of the materials were locally sourced from the site. Unlike the 3DP-C and conventional scenarios where both had the highest ratio of 100 %, where all the materials were imported. This paper contributes by highlighting the potential of 3DP-E to enhance sustainability by reducing the environmental impact of construction.